2D difference gel electrophoresis reference map of a Fusarium graminearum nivalenol producing strain. Issue 4 (22nd January 2013) - Pasquali, Matias; Serchi, Tommaso; Renaut, Jenny; Hoffmann, Lucien; Bohn, Torsten
<x xml:space="preserve">Abstract</x> Fusarium graminearum is widely studied as a model for toxin production among plant pathogenic fungi. A 2D DIGE reference map for the nivalenol‐producing strain 453 was established. Based on a whole protein extract, all reproducible spots were systematically picked and analyzed by MALDI‐TOF/TOF, leading to the identification of 1102 protein species. The obtained map contributes to the annotation of the genome by identifying previously nondescribed hypothetical proteins and will serve as a reference for future studies aiming at deciphering F. graminearum biology and chemotype diversity.